2020
DOI: 10.1371/journal.ppat.1008666
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo characterization of a recombinant rhesus cytomegalovirus containing a complete genome

Abstract: Cytomegaloviruses (CMVs) are highly adapted to their host species resulting in strict species specificity. Hence, in vivo examination of all aspects of CMV biology employs animal models using host-specific CMVs. Infection of rhesus macaques (RM) with rhesus CMV (RhCMV) has been established as a representative model for infection of humans with HCMV due to the close evolutionary relationships of both host and virus. However, the only available RhCMV clone that permits genetic modifications is based on the 68–1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 109 publications
1
55
0
Order By: Relevance
“…SIV insert (SIVgag, retanef, 5'pol)-expressing vaccine vectors based on RhCMV 68-1 (GenBank #MT157325) have been described previously (6,33). All other RhCMV constructs used in this study were based on either the partially-repaired RhCMV 68-1.2 strain (GenBank #MT157326) or our fully reconstructed FL RhCMV clone (GenBank #MT157327) (13,18). Following the original 68-1 vector design, SIV inserts were introduced into the Rh211 open reading frame (ORF) in RhCMV 68-1.2 and transgene expression was driven by an EFIα promoter.…”
Section: Generation Of Recombinant Rhcmv Vectorsmentioning
confidence: 99%
“…SIV insert (SIVgag, retanef, 5'pol)-expressing vaccine vectors based on RhCMV 68-1 (GenBank #MT157325) have been described previously (6,33). All other RhCMV constructs used in this study were based on either the partially-repaired RhCMV 68-1.2 strain (GenBank #MT157326) or our fully reconstructed FL RhCMV clone (GenBank #MT157327) (13,18). Following the original 68-1 vector design, SIV inserts were introduced into the Rh211 open reading frame (ORF) in RhCMV 68-1.2 and transgene expression was driven by an EFIα promoter.…”
Section: Generation Of Recombinant Rhcmv Vectorsmentioning
confidence: 99%
“…We next asked the question of whether abrogating both the PRC and non-PRC-related immune programming activities of Rh157.5 and Rh157.4 was sufficient to convert a wildtype-like RhCMV, with conventional MHC-Ia-restricted CD8 + T cell targeting, to a 68-1-like vector with exclusively MHC-IIand MHC-E-restricted CD8 + T cell responses. Using sequence information from primary RhCMV isolates, including the original 68-1 isolate (17), we reconstructed a full length RhCMV clone (RhCMV FL) in which all suspected deletions, inversions, frameshifts and premature termination codons affecting viral open reading frames were repaired and the Rh13.1 open reading frame (ORF) was replaced by an SIVgag insert (18). RhCMV FL has robust in vivo spread (18), and as expected for a wildtype genetic configuration (9), elicits MHC-Ia-restricted, CD8 + T cell responses (Fig.…”
mentioning
confidence: 99%
“…Using sequence information from primary RhCMV isolates, including the original 68-1 isolate (17), we reconstructed a full length RhCMV clone (RhCMV FL) in which all suspected deletions, inversions, frameshifts and premature termination codons affecting viral open reading frames were repaired and the Rh13.1 open reading frame (ORF) was replaced by an SIVgag insert (18). RhCMV FL has robust in vivo spread (18), and as expected for a wildtype genetic configuration (9), elicits MHC-Ia-restricted, CD8 + T cell responses (Fig. 2A).…”
mentioning
confidence: 99%
“…A stock of the resulting virus was used to construct a primary BAC (RhCMV 68−1 BAC) 17 , from which all available RhCMV BACs are derived. A succession of studies has shown that RhCMV 68−1 and RhCMV 68−1 BAC are highly mutated [18][19][20][21][22][23] , with the detail having been revealed progressively by the genome sequences of RhCMV 68−1 , RhCMV 68−1 BAC, derivatives of RhCMV 68−1 BAC, viruses generated from RhCMV 68−1 -based BACs, and other RhCMV strains (Table 1). As a result, RhCMV 68−1 and RhCMV 68−1 BAC lack the functions of many genes required for cellular tropism and tness in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In order to ensure that the RhCMV component of the repaired RhCMV 68−1 /EBOV BAC was as close in sequence as possible to the original RhCMV 68−1 genome as perceived to have existed prior to isolation and serial passage in cell culture 25 , it was necessary to identify mutations in RhCMV 68−1 BAC (and hence in RhCMV 68−1 /EBOV BAC) that have resulted in inactivated ORFs. This involved detailed examination of an alignment of all available RhCMV genome sequences, which at the time did not include several reported since by Taher et al (2020) 23 ; these recent sequences were incorporated at the end of the study and identi ed no additional mutations. This comparative exercise revealed a total of 13 putatively inactivated ORFs (Table 2).…”
Section: Resultsmentioning
confidence: 99%